The Battle of Bangui: The inside story of South Africa's worst military scandal since Apartheid - Kleynhans, Evert (Scientia Militaria - South African Journal of Military Studies, 2021)
The Battle of Bangui has assumed near mythical proportions within South Africa,and specifically in the South African National Defence Force (SANDF). During thebattle that occurred in March 2013, a small force of crack South African troops engaged a7 000-strong Seleka rebel force in an effort to stem their advance on Bangui – the capitalof the politically unstable and resource-rich Central African Republic (CAR). Over thecourse of two days, the South African force fought a number of gallant actions andinflicted heavy casualties on the advancing rebel forces. However, the South Africanscould not hold out indefinitely, especially against overwhelming odds and after takingsome casualties during the ensuing fighting. Moreover, they soon found themselvessurrounded in their makeshift base within Bangui, where they were ultimately forced tonegotiate a ceasefire with the Seleka rebels. Following the ceasefire, the South Africancontingent returned to South Africa, and so began the process of trying to make senseof the rationale to deploy SANDF troops to CAR, and what exactly happened duringthe so-called ‘Battle of Bangui’. Most importantly, the country, the defence force, andthe respective families, had to come to grips with the unnecessary loss of South Africanlives in a seemingly distant corner of Africa.